1995
DOI: 10.3382/ps.0741470
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Early Nutrient Restriction on Broiler Chickens.

Abstract: An experiment was conducted to determine the effect of two early nutrient restriction programs on performance, selected characteristics of the gastrointestinal tract (GIT), and activities of digestive enzymes of broiler chickens. Three hundred and sixty male broiler (Ross x Ross) chicks kept in floor pens were assigned to three groups. The control group (C) was given ad libitum access to feed from 1 to 48 d of age. Another group was restricted from 11 to 14 d (R4) of age to an energy intake of .74 x BW.67 kcal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 24 publications
3
15
1
2
Order By: Relevance
“…These observations support the findings of Palo et al (1995) who reported that carcass and breast yields were not affected in two early feed-restriction programs. Similarly, Dozier et al (2003) confirmed these findings.…”
Section: Discussionsupporting
confidence: 82%
“…These observations support the findings of Palo et al (1995) who reported that carcass and breast yields were not affected in two early feed-restriction programs. Similarly, Dozier et al (2003) confirmed these findings.…”
Section: Discussionsupporting
confidence: 82%
“…It has been known that feed restricted birds consumed more feed in their attempt to compensate for the time they would have been deprived of feed (Khetani et al, 2009). In contrast, Palo et al (1995) observed that feed restricted birds gained less weight than full-fed control birds. The possible explanation of the lower body weight observed in the feed restricted birds may be the decrease in The highest FCR in birds fed with control (T1) diet and the lowest FCR in birds fed with 70% diet (T4) could be due to significantly higher and lower feed intakes of birds, respectively.…”
Section: Resultsmentioning
confidence: 40%
“…Alkaline phosphatase is a complex enzyme, related to secondary ossification, osteoblastic activity; moreover, it is produced in the intestinal brush border. In this regard PALO et al (1995) reported an activity peak in broilers at the age of 2 weeks, corresponding to the exhaustion of the yolk sac as well as to the establishment of locomotory independence. An early peak, and the latter continuous activity reduction was moreover described by SZABÓ et al (2005), along the entire rearing course of heavy weight turkeys.…”
Section: Serum Enzymesmentioning
confidence: 99%